Identification of high blanchability donors, candidate genes and markers in groundnut - Shah, Priya; Gangurde, Sunil S.; Ramachandran, Senthil; Singam, Prashant; Ovais Hamid Peerzada; Janila, Pasupuleti; Singh, Kuldeep; Mayes, Sean; Pandey, Manish K. (BioMed Central Ltd., 2025)
Blanchability is the ability of seeds to shed their seed coat (testa) and is a trait of economic importance in the food processing industry, yet remains underexplored in breeding programs. In this study, blanchability was evaluated in 184 groundnut accessions from the ICRISAT minicore collection to identify associated genomic regions, candidate genes, and molecular markers. Significant variability was observed over two seasons, with values ranging from 3.98 to 70.08%. Ten genotypes, including ICG10890, ICG9507, ICG13982, and ICG297, showed high blanchability, with ICG297 emerging as a promising donor based on cluster analysis of blanchability and agronomic traits. Genome-wide associations study (GWAS) using the 58 K ‘Axiom_Arachis’ SNP array revealed 58 significant SNP-trait associations, highlighting important genes such as isocitrate dehydrogenase and ubiquitin ligase, which influence seed coat structure and cell wall integrity thereby affecting blanchability. Further, nine SNPs were selected via allele mining, among these four SNPs, on chromosomes A01 (snpAH00551, AhBL01), A06 (snpAH00554, AhBL02), B04 (snpAH00558, AhBL03), and B07 (snpAH00559, AhBL04), effectively distinguishing between high and low blanchability genotypes. These validated SNPs present valuable tools for genomics-assisted breeding. Overall, the finding contributes towards better understanding of the genetic basis of blanchability in groundnut, providing key genomic resources for improving processing-related traits.